Möglichkeiten der spezialisierten ambulanten Palliativversorgung - Geist, Marcus Julian Peter; Bardenheuer, Hubert J.; Weigand, Markus A.; Frankenhauser, Susanne; Keßler, Jens (Der Urologe, 2018)
Palliative care patients with incurable advanced disease suffering from complex symptoms can receive specialized outpatient palliative care in addition to the existing ambulatory care system. Qualified physicians and nurses care for patients and their dependents in cooperation with other professionals. In addition to a 24/7 on-call service for emergencies or acute crises, patients and their dependents are offered regular visits.
Gesehen am 11.12.2019